Design a Free Energy System (Second Model) - Fatima Mohammed Shakhir Najm; Safa abdulah Jasim Hussein; Mohammed jasim mohammed abas; Afrah Mohamed Aboud Turky; Rusul abd-alameer hmoud Salman (Genius Journals, 2024)
The diode is placed on the transistor so that the negative end of the diode is to the left of the transistor, and the second diode is connected to the collector © of the transistor, where the negative end of the diode is at the bottom. Then we connect the 100-ohm resistor to the base end of the transistor (B), then the 5K resistor we connect its first and second ends. With the end of the diode, while winding the coil, which is clockwise at the beginning of the winding, two wires are output, one of which is thick (0.23) and the other is thin (0.25). At the end of the winding, two wires of the same type also come out. We will take the thin wire located at the beginning of the coil and connect it to the emitter terminal (E) of the transistor, while the thick wire located at the beginning of the coil connects to the collector terminal ((C)) of the transistor (it must be placed before the diode). As for the two wires Coming out of the coil, the thin wire will be connected to the variable resistor with its third terminal, while the thick wire will be connected to the positive terminal of the battery, and either the terminal or the negative terminal of the battery will be connected to the emitter terminal ((E)) of the transistor
Keywords: Energy System; diode; collector terminal